2018
DOI: 10.1016/j.placenta.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic glucose enhanced MRI of the placenta in a mouse model of intrauterine inflammation

Abstract: DGE-MRI is useful for evaluating placental functions related to glucose utilization. The technique uses a non-toxic biodegradable agent (d-glucose) and thus has a potential for rapid translation to human studies of placental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The conventional onVDMP sequence is composed of a train of binomial pulses followed by an image acquisition module, as shown in Figure 1(b). 1820 As a previous VDMP study suggested, 21 the fast-exchanging signal component decays during the mixing time. Hence, the mixing time between binomial pulses was set to zero in this study of hydroxyl groups in D-glucose under physiological conditions and the offset of the binomial pulses was set to the water resonance.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…The conventional onVDMP sequence is composed of a train of binomial pulses followed by an image acquisition module, as shown in Figure 1(b). 1820 As a previous VDMP study suggested, 21 the fast-exchanging signal component decays during the mixing time. Hence, the mixing time between binomial pulses was set to zero in this study of hydroxyl groups in D-glucose under physiological conditions and the offset of the binomial pulses was set to the water resonance.…”
Section: Methodsmentioning
confidence: 80%
“…Among various glucoCEST methods, on-resonance variable delay multiple pulse (onVDMP) MRI is promising due to its excellent labeling efficiency and sensitivity. 1820 In this study, we applied onVDMP MRI to detect cerebral D-glucose uptake and CSF clearance in AD mice and demonstrate its feasibility in discriminating AD from normal mice.…”
Section: Introductionmentioning
confidence: 99%
“…S1A. The basic composition of the saturation module is a train of high-power binomial pulses (bp) with zero-bp interval and zero water resonance offset (22,35,36). The pulse shape was two bp, and the number of pulse pairs was four.…”
Section: Mri Experimentsmentioning
confidence: 99%
“…For example, studies have shown that, in the brain tumors, the increase of glucoCEST signal correlates well with the changes in cerebral blood volume, glucose transporter, and BBB integrity [ 70 , 110 , 111 ]. GlucoCEST contrast has been suggested as an imaging biomarker for tumor aggressiveness [ 61 ] and inflammatory responses in the kidney [ 112 ] and placenta [ 113 ].…”
Section: Nutrients and Supplements For Cest Mrimentioning
confidence: 99%